Vertical Thin Film Transistor Based on Conductivity Modulation of Graphene Electrode by Micro‐Hole Patterning - Goeun Pyo; Gwang Jun Lee; Seungchul Lee; Jae Hoon Yang; Su Jin Heo; Gyeong Hyeon Choi; SeungNam Cha; Jae Eun Jang (Advanced Electronic Materials, 2022)
Abstract The vertical thin film transistor (VTFT) has several advantages over the planar thin film transistor, such as a high current density and low operating voltage, because of the structural specificity. However, it is difficult to realize transistor operation in a VTFT because of the structural limitation that the gate field is blocked. As a solution, the conductivity modulation of a graphene electrode is studied with a micro‐hole structure as a gate field transfer electrode. The micro‐hole array pattern in the graphene allows better penetration of the gate field to junction and the work function to be modulated. Moreover, the patterning induces a doping effect on the graphene which results in a high barrier at the p–n junction and improves the conductivity in the device operation. The optimum performance is shown at 5 µm hole size and 30% hole ratio by analyzing the hole size and the area ratio. The proposed structure shows about 20 times higher on‐current than a planar transistor with a same active area. Compared to a VTFT using simple graphene working function modulation, the proposed structure has an on‐state current that is ten times higher and off‐state current that is reduced 50%, and therefore has an improved on–off ratio.